THE EFFECTS OF THE QUALITY SERVICE AND THE CUSTOMER LOYALTY UPON THE REVENUE OF TELKOM COOPERATION UNIT BOGOR - Dede Suparman (The Management Journal of Binaniaga, 2017)
Objective of this research is to identify whether the quality of the product and the customers loyalty have affected the revenue of Telkom Cooperation Bogor either simultaneously or partly.The population are the customers of Telkom Cooperation Bogor which is 240 people. Sampling has applied slovin formulation with 5% error rate resulting 150 respondents.Instrument of this research is the questionnaires. Collected data has been processed using a simple regression analysis technique and multiple regression applying SPSS (Statistical Package for Social Science).The result of the research has indicated that: First, the quality of a service has positively and significantly affected the revenue refers to the regression function Y = 38.598 + 0.532X1, it explains that when the quality of service is constant or X1 = 0, the revenue will be 38.598. Coefficient beta (b1) is 0.532 indicating that when the quality of service is increased 1 point, the revenue will increase 0.532. Second, the customers’ loyality has positively and significantly affected the revenue refers to the regression function Y = 43.333 + 0.467X2, it means that when the customers loyality is constant or X2 = 0, the revenue will be 43.333. Coefficient beta (b2) is 0.467 indicating that when the customers’ loyalty is increased 1 point, the revenue will increase 0.467. Third, both the quality of a service and the customers loyalty have positively and significantly affected the revenue refers to the multiple regression function Y = 26.760 + 0.412X1 + 0.191X2 which explaining: The value of 0.412 is the coefficient value of variable X1 for b1 value refers to the equations of multiple linear regression Y = a+b1X1+b2X2 and b1 = 0.412 identifying that every increasing of 1 point of the quality of service will obviously affect the revenue of 0.412 points and other independent variables are constant. The value of 0.191 is the coefficient value of variable X2 for b2 refers to the equations of multiple linear regression Y = a+b1X1+b2X2 and b2 = 0.191, explaining that every increasing of 1 point of the customers’ loyalty will affect the revenue of 0.191 point and the other independent variables are constant. Nevertheles the value of 26.760 is constant for the a value which is Y value when X = 0. The + (positive) token on the variable of the quality of service and the customers’ loyalty. The percentage value of the quality of service variable and the customers loyalty upon the revenue has obtained the Adjusted R Square value of 0.405 or (40.5%). It has indicated that the percentage of the effect of independent variable which is both the quality of service and the customers loyalty have affected the revenue 40.5%, moreover the remaining of 59.5% has been affected by other variables which are not included in this research.Keywords : The Quality of Service, the Customer Loyalty and Revenue.